DEALER MOBIL PREMIUM DI BANJARBARU - Ahmad Arifin Abrory Prima; Irwan Yudha Hadinata (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The presence of premium cars in South Kalimantan is increasing. But, instead of bringing benefits to the region in fact it doesn’t. Premium cars roaming South Kalimantan still use out-of-region number plates. Vehicle Tax (PKB) for premium cars which should go to the regional treasury of South Kalimantan Province actually flows to the region where the car is registered. This of course brings big losses. This happens because there are no premium car dealerships in South Kalimantan, so people like to buy premium cars outside the region. To overcome this, a premium car dealership is needed in South Kalimantan. To attract buyers, a premium car dealership should not just be a place to buy premium cars, but also offer a premium car buying experience. This premium experience can be created through Futuristic Architecture and Mix-Used and Open Plan concepts. With a car dealership that is able to provide a premium experience, people will be more interested in buying premium cars in South Kalimantan, which will increase regional income through PKB and bring economic benefits to South Kalimantan Province.